Case Report: Onset of Takotsubo syndrome during a heart rehabilitation session - Jiménez-Jiménez, Ana Belén; Muñoz-Paz, Javier; Ladera-Santos, Diana; Heredia-Torres, Ángela; Caballero-Villarraso, Javier; Mayordomo-Riera, Fernando (Frontiers in Cardiovascular Medicine, 2025)
Takotsubo syndrome (TTS) is an acute cardiac condition characterized by transient regional left ventricular systolic dysfunction. Traditionally, it has been associated with physical or psychological stressors. Clinically, the onset of TTS is similar to acute coronary syndrome, requiring appropriate differential diagnosis to distinguish between the two clinical entities. Its treatment is usually conservative, and the prognosis is generally favorable. We report the case of a 57-year-old woman who was referred to the Department of Rehabilitation after suffering a non-ST-segment elevation myocardial infarction. During her eighth physical rehabilitation session, she developed palpitations and hypertension. Initial telemetry monitoring showed ventricular bigeminy with extrasystoles, tachycardia episodes, and ST-segment elevation. She was admitted to the Department of Cardiology, and cardiac catheterization and subsequent coronary angiography were performed, revealing no incidence of coronary lesions. However, ventriculography demonstrated severe left ventricular dysfunction in the systolic phase, characterized by akinesia of the mid-apical segments. These findings were suggestive of Takotsubo syndrome, which was subsequently confirmed by cardiac magnetic resonance imaging.